Pengembangan Merchandise Untuk Branding Universitas Menggunakan 3D Printing - Siti Mardiyah; Julian Anindito Widiatmoko; Her Tafga Arfanindita; Welly Mahardhika; Husna Nadiya Asy Syahidah; Ikhsanudin Meinanda (Program Studi Teknik Industri Universitas Setia Budi, 2026)
Merchandise serves as a branding medium that can be utilized to build the image of an organization, including higher education institutions. However, merchandise development in universities is often still generic and has not optimally explored institutional identity elements in an integrated manner, nor has it been widely examined from the perspective of user perception toward design and production technology. This study aims to develop a merchandise product in the form of a keychain that represents the identity of Universitas Tidar, while also evaluating the influence of design and 3D printing technology information on user perception. Two keychain designs were developed based on the identity elements of Universitas Tidar and realized into 3D models using CAD software, then fabricated using 3D printing technology. The evaluation was conducted through a questionnaire involving 440 student respondents based on four aspects: identity, usability, quality, and aesthetics, while considering differences in information treatment regarding the production process. The results indicate that both designs received generally positive ratings, with no statistically significant difference between them. In addition, providing information about the use of 3D printing technology did not significantly influence respondents’ perceptions. Further findings reveal that color is the most dominant factor affecting respondents’ evaluations, particularly in representing the university’s visual identity. Therefore, selecting colors that are more aligned with the identity of Universitas Tidar should be prioritized in future design development to enhance the effectiveness of merchandise as a branding medium.